2023
DOI: 10.1186/s11658-023-00448-7
|View full text |Cite
|
Sign up to set email alerts
|

CircRNF10-DHX15 interaction suppressed breast cancer progression by antagonizing DHX15-NF-κB p65 positive feedback loop

Abstract: Background Breast cancer (BC) is a common threat to women. The continuous activation of nuclear factor kappa B (NF-κB) signaling pathway contributes to the development of BC. This study aimed to investigate the role of a circular RNA (circRNF10) in BC progression and regulating NF-κB signaling pathway. Methods Bioinformatics analysis, RT-qPCR, subcellular fractionation, FISH, RNase R treatment, and actinomycin D assay were used to explore the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…P38, as a stress-related protein kinase, is an important enzyme of MAPK signaling pathway (Falcicchia et al 2020). The heterodimers formed by P65 are responsible for gene transcription when activating the canonical NF-κB signaling pathway (Zheng et al 2023), and the activation of canonical NF-κB is closely related to the inflammatory response. The research demonstrated that through downregulating the NF-κB and MAPK pathways induced by L. monocytogenes, bacteriocins may inhibit the expression of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…P38, as a stress-related protein kinase, is an important enzyme of MAPK signaling pathway (Falcicchia et al 2020). The heterodimers formed by P65 are responsible for gene transcription when activating the canonical NF-κB signaling pathway (Zheng et al 2023), and the activation of canonical NF-κB is closely related to the inflammatory response. The research demonstrated that through downregulating the NF-κB and MAPK pathways induced by L. monocytogenes, bacteriocins may inhibit the expression of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small portion of them can play a role in promoting tumor growth by encoding or binding proteins, including circCAPG/CAPG-171aa [ 76 ] , circEIF6/EIF6-224aa [ 77 ] , circKIF4A/EIF4A3 [ 70 ] , CircSNX25/COPB1 [ 71 ] , and circEIF3H/IGF2BP2 [ 73 ] . There are also some circRNAs whose expression levels were low in TNBC, such as CircPTK2 [ 51 ] , CircNR3C2 [ 58 ] , circFBXW7 [ 11 ] , circRNF10 [ 85 ] , and circCCDC85A [ 86 ] . Overexpressing these circRNAs greatly reduces the ability of TNBC cells to grow and vice versa.…”
Section: The Role Of Circular Rna In Tnbc Progressionmentioning
confidence: 99%
“…The common metastases of TNBC include brain, liver, lung, and bone metastasis, which ultimately leads to a high mortality rate due to the presence of lesion metastasis in different parts and degrees. Many circRNAs are highly expressed in TNBC, such as circRRM2 [80] , circ0000851 [81] , circEZH2 [82] , circ0042881 [83] , and circZFAND6 [84] [Table 1]. A majority of them can enhance the miRNA sponge function, thus promoting the proliferation, migration, and invasion ability of TNBC, including circ0000851/ miR-1183 [48] , circEZH2/miR-217-5p [82] , circ0042881/miR-217 [83] , and circZFAND6/miR-647 [84] , thereby increasing tumor growth.…”
Section: The Role Of Circular Rna In Tnbc Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, p65 enhances the transcription of DHX15 in the nucleus to increase its levels. However, circRNF10 suppresses the DHX15/p65 complex to impair its nuclear transfer and suppress the NF-κB axis [ 233 ]. Table 3 and Fig.…”
Section: Epigenetic Regulation Of Nf-κb By Non-coding Rnasmentioning
confidence: 99%